1979
DOI: 10.1007/bf00267267
|View full text |Cite
|
Sign up to set email alerts
|

DNA Supercoiling and transcription in Escherichia coli: Influence of RNA polymerase mutations

Abstract: Coumermycin A1, a specific inhibitor of DNA gyrase, differentially changes the spectrum of proteins synthesized in wild type E. coli cells but has no effect on the protein spectrum in mutant cells with coumermycin-resistant DNA gyrase. The rpoB265 mutation affecting RNA polymerase decreases the coumermycin A1-sensitivity of bacteria while the rpoC3 mutation increases it. The interaction of wild type and mutant RpoB265 RNA polymerases with ColEl plasmid DNA in vitro is differently affected by DNA supercoiling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Two-dimensional protein gel electrophoresis of E. coli gyrB mutants, which have a 25% steady-state decrease in the level of supercoiling, showed that 45 of 90 proteins had altered synthesis rates (7). Most proteins affected by the lowered levels of supercoiling showed an increase in abundance, consistent with our findings and those of Mirkin et al (21). In further agreement, Menzel and Gellert have observed that 4 of 20 random promoters shotgun cloned into a pKO1 plasmid were strongly induced by the addition of coumermycin A1 (19).…”
Section: Discussionsupporting
confidence: 93%
“…Two-dimensional protein gel electrophoresis of E. coli gyrB mutants, which have a 25% steady-state decrease in the level of supercoiling, showed that 45 of 90 proteins had altered synthesis rates (7). Most proteins affected by the lowered levels of supercoiling showed an increase in abundance, consistent with our findings and those of Mirkin et al (21). In further agreement, Menzel and Gellert have observed that 4 of 20 random promoters shotgun cloned into a pKO1 plasmid were strongly induced by the addition of coumermycin A1 (19).…”
Section: Discussionsupporting
confidence: 93%
“…Contradictory results concerning the effects of these inhibitors on the differential rate of tryptophanase synthesis have been reported (Shuman and Schwartz, 1975;Sanzey, 1979). Inactivation of gyrase enhanced promoter activities in several other cases too (Mirkin et al, 1979;Fairweather et al, 1980;DiNardo et al, 1982). Inactivation of gyrase enhanced promoter activities in several other cases too (Mirkin et al, 1979;Fairweather et al, 1980;DiNardo et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial indications that superhelical viral DNA can be more efficiently transcribed than relaxed DNA both in vitro (25) and in vivo (42), much evidence that DNA superhelicity affects transcription initiation has accumulated; most promoters are best transcribed from supercoiled templates, while some are best transcribed from relaxed ones (for reviews, see references 10, 18, 53, and 54). A related observation is that mutations in the gene for the d subunit of RNA polymerase (rpoB) can suppress the defective initiation of transcription and replication produced by a number of DNA gyrase mutations (11,13,35). Furthermore, rpoB mutations and treatment of wild-type strains with rifampin (which binds to the 1 subunit of RNA polymerase) can alter the degree of dependence of transcription initiation on superhelicity (11,13,35).…”
mentioning
confidence: 99%
“…A related observation is that mutations in the gene for the d subunit of RNA polymerase (rpoB) can suppress the defective initiation of transcription and replication produced by a number of DNA gyrase mutations (11,13,35). Furthermore, rpoB mutations and treatment of wild-type strains with rifampin (which binds to the 1 subunit of RNA polymerase) can alter the degree of dependence of transcription initiation on superhelicity (11,13,35).…”
mentioning
confidence: 99%